A niche analysis of two channels of open government information: online and offline. Issue 4 (2nd October 2021) - Zhang, Yu
Abstract : With the rapid development and wide popularization of information and communication technology (ICT), two trends in the policy implementation process of open government information channels have emerged: online and offline. This research uses an implementation behavior theoretical framework and panel data of 31 provincial governments in mainland China from 2008–2017 to compare and analyze the factors influencing the implementation of online and offline channels. The results demonstrate that over 10 years, online channels have replaced offline channels as the main channels of open government information and that there are significant differences in the influence of different factors on the online and offline channels. Upward pressure and internal willingness do not significantly impact offline channels but have partially significant positive effects on online channels. Citizen participation and the regional environment have significant effects on online and offline channels, but the effects are inconsistent. The findings add to the literature on the implementation of different policy elements in the field of policy science, providing a decision-making reference for governments to adjust and balance the implementation process between online and offline channels.